TEKNIK BUDIDAYA UDANG DENGAN SISTEM POLIKULTUR DI KELURAHAN TAMARUPA KEC. MANDALLE KABUPATEN PANGKEP - Saenong, Muhammad; Harlina, Harlina (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, 2022)
Pangkajene Islands Regency is a coastal area where most of the population depends on their life as aquaculture farmers. In this village there is a farmer group